2021
DOI: 10.1136/jmedgenet-2021-108065
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnoses in the congenital malformations caused by ciliopathies cohort of the 100,000 Genomes Project

Abstract: BackgroundPrimary ciliopathies represent a group of inherited disorders due to defects in the primary cilium, the ‘cell’s antenna’. The 100,000 Genomes Project was launched in 2012 by Genomics England (GEL), recruiting National Health Service (NHS) patients with eligible rare diseases and cancer. Sequence data were linked to Human Phenotype Ontology (HPO) terms entered by recruiting clinicians.MethodsEighty-three prescreened probands were recruited to the 100,000 Genomes Project suspected to have congenital ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In summary, the ciliopathies provide an exemplar group of disorders that illustrate both the challenges and opportunities of working with 100K datasets (Best et al, 2021; Wheway et al, 2019). 100K remains an immensely valuable clinical and scientific resource with huge potential for patient benefit, but that benefit has not yet been fully realized.…”
Section: Future Use Of 100k Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, the ciliopathies provide an exemplar group of disorders that illustrate both the challenges and opportunities of working with 100K datasets (Best et al, 2021; Wheway et al, 2019). 100K remains an immensely valuable clinical and scientific resource with huge potential for patient benefit, but that benefit has not yet been fully realized.…”
Section: Future Use Of 100k Datamentioning
confidence: 99%
“…Tier 3 and un-tiered variants are not inspected routinely by NHS diagnostic labs, and left to external researchers to consider more fully, if at all. In our own work (Best et al, 2021), we identified 11/83 probands (13.3%) with research molecular diagnoses with at least one variant outside of tiers 1 and 2. Five tier 3 variants and 12 untiered variants contribute to the diagnoses for these 11 participants.…”
Section: Tiering Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…CEP290 has over 200 associated pathogenic variants spread throughout the full length of the gene. There are also 136 affected probands in the 100,000 Genomes Project datasets with biallelic likely pathogenic CEP290 variants and ciliopathy phenotypes (4, 5). However, there is no clear genotype-phenotype association between severe syndromic and isolated retinal disease-causing genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Ciliopathies are a heterogenous group of at least 25 inherited disorders with clinically overlapping phenotypes, caused by pathogenic variants in >200 genes ( 13 , 14 ). Ciliopathies affect many organ systems, causing a broad range of clinical phenotypes of varied severity and penetrance that include cystic kidneys, retinal dystrophy, bone abnormalities, organ laterality defects, respiratory tract defects, infertility, obesity, neurodevelopmental defects and cognitive impairment ( 15 ).…”
Section: Introductionmentioning
confidence: 99%